Impact assessment of job characteristics model on employee engagement / Nurul Hidayah Mohd Nadhir and Fadilah Puteh - Mohd Nadhir, Nurul Hidayah; Puteh, Fadilah (2017)
This paper discusses on the impact assessment of job characteristics model (JCM) on employee engagement. The final version of Hackman and Oldham's JCM in 1980 was adapted in this study. The JCM five core elements namely skill variety, task identity, task significance, autonomy, and feedback were assessed to investigate their impact on employee engagement. A structured questionnaire was employed to collect the data. Data was collected from 234 respondents from public service employees of Ministry of Tourism and Culture, Malaysia. Data was analysed using SPSS. Based on the findings, it was found that only three JCM core elements influenced employee engagement namely feedback (β = .414, p < 0.00), task significance (β = .231, p < 0.05) and skill variety (β = .140, p < 0.05).